2022
DOI: 10.2147/dddt.s348335
|View full text |Cite
|
Sign up to set email alerts
|

Yishen Qingli Heluo Granule in the Treatment of Chronic Kidney Disease: Network Pharmacology Analysis and Experimental Validation

Abstract: Background Chronic kidney disease (CKD) is considered a global public health problem with high morbidity and mortality. Yishen Qingli Heluo granule (YQHG) is representative traditional Chinese medicine (TCM) remedy for clinical treatment of CKD. This study aims to explore the mechanism of YQHG on CKD through network pharmacology and experimental validation. Methods Traditional Chinese Medicine Systems Pharmacology (TCMSP) database and wide-scale literature mining were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Research on the relationship between kaempferol, isorhamnetin, myricetin, and CKD is sparse. Some network-based pharmacological studies suggest that kaempferol and myricetin may have protective effects on renal function, offering new perspectives for the development of new CKD treatment ( 48 , 49 ). However, this study did not find a correlation between the intake of myricetin or kaempferol and the incidence of CKD, indicating a need for further research to determine the causal relationship between the consumption of kaempferol or myricetin and CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the relationship between kaempferol, isorhamnetin, myricetin, and CKD is sparse. Some network-based pharmacological studies suggest that kaempferol and myricetin may have protective effects on renal function, offering new perspectives for the development of new CKD treatment ( 48 , 49 ). However, this study did not find a correlation between the intake of myricetin or kaempferol and the incidence of CKD, indicating a need for further research to determine the causal relationship between the consumption of kaempferol or myricetin and CKD.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study did not find a correlation between the intake of myricetin or kaempferol and the incidence of CKD, indicating a need for further research to determine the causal relationship between the consumption of kaempferol or myricetin and CKD. Regarding isorhamnetin, some studies found that isorhamnetin can improve TGF-β1-induced glycolysis and renal fibrosis ( 48 , 49 ). This study found an association between high isorhamnetin intake and a lower incidence of CKD, suggesting that isorhamnetin may benefit CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“… 91 In CKD, PTGS2 is involved in the regulation of inflammatory factors accumulation in target organs, which consequently induces tissue fibrosis. 92 Although AR has been studied quite extensively in the field of cancer, there are few reports of its effects on RF and hence, no experimental validation was performed. In accordance with these previous reports, our molecular docking and MD simulations demonstrated that IL-1β, IL-6, TNF-α, PTGS2, and AR are were involved in therapeutic mechanism of YSHXD in RF.…”
Section: Discussionmentioning
confidence: 99%
“… Details of Yishen Qingli Heluo Granule (YQHG) [ 12 ]: (1) the genus; (2) parts used; (3) dose used (g). …”
Section: Figurementioning
confidence: 99%
“…Bidirectionally, TCM herbs or herbal extracts can also remodel the diversity of gut microbiota to alleviate related diseases [ 11 ]. Several recent studies have determined that TCM can significantly influence the progression of CKD [ 12 , 13 ]. However, there is still a lack of a comprehensive summary of the effects and mechanisms of TCM on CKD from the perspective of microecology.…”
Section: Introductionmentioning
confidence: 99%